Literary understandings of the Bible: the deconstructionist approach - Hunter, Jannie (Old Testament essays, 1994)
Special Edition: Understanding the Old Testament in South Africa. The deconstructionist approach to the interpretation of texts is a challenging one, using the language of the text to illustrate the impossibility of arriving at clear, unambiguous meaning. It aims at indicating that written language functions differently from direct communication because it lacks the immediacy of the presence of the author and the audience involved. Written language is open to misinterpretation and the Bible as a written document also has to take note of the claims of deconstruction.